Formação de professores na escola: a atuação da gestão escolar para a profissionalização docente - Pedroso, Margareth (Universidade Federal de São Carlos, 2022)
This research has as its theme the training of teachers at school, school management and teacher professionalization, and assumes that teacher training at school is essential for the professional development of teachers and that school management has a preponderant role in the organization of training processes with with a view to professionalization. The research was mobilized by the following question: what elements of school management performance enable the training of teachers with a view to teaching professionalization? As a general objective, it was intended to understand, from the perspective of professionalization, how school management organizes the formative processes that occur at school. In order to organize the research, this central objective was subdivided into four specific objectives, namely: a) to verify, in the legislation and guiding documents of the municipal teaching network of Sorocaba, evidence of teacher training aimed at teaching professionalization; b) understand the teacher training movements at school aimed at teaching professional development; c) identify and analyze the announced formative processes that occur in the times and spaces of the school and d) identify and analyze declared elements of the performance of the school management related to the development of formative actions that aim at the professionalization of teachers in the municipal teaching network of Sorocaba. We dialogued with different literature sources to deal with training at school, teacher professional development, professionalism and professionalization and to reflect on school management in relation to training at school and teacher professionalization. The research was qualitative, using a questionnaire and an interview to produce data, in addition to document analysis. We build the analysis steps based on content analysis. The research scenario is located in the municipal education network of Sorocaba, with the teachers and management teams of elementary schools in this network as participants and collaborators. The final results sought to compose a dialogical reflection between the analysis of the research corpus and the theoretical framework that supported it. It was possible to verify that: a) the legal and guiding documents of the municipal education network compel the carrying out of continuous training of its professionals, through reflective and participatory training processes; b) in the analyzed universe, it is noticed that there are actions of organization of times and training spaces by the management team of the school that can enable the teaching professionalization; c) the conception of teacher education directly influences the organization of training times and spaces at the school; d) the conscious participation of teachers in the school's training processes, from their preparation to evaluation, enables the development of teaching professionalism and professionalization and f) the performance of school management has a preponderant role in the training of school teachers for the development of teaching professionalism.
Teacher training at school: the performance of school management for teacher professionalization
Keywords: Desenvolvimento profissional; Profissionalidade; Profissionalização; Formação na escola; Gestão escolar; Professional development; Professionality; Professionalization; School training; School management; CIENCIAS HUMANAS::EDUCACAO